Comparative potentials of H2- and O2-MBfRs in removing multiple tetracycline antibiotics - Salman, Meric Yilmaz; Taskan, Ergin; Hasar, Halil (Elsevier, 2022)
Tetracycline antibiotics are broad spectrum antimicrobial compounds commonly used in human therapy and animal growth. This study has focused on the simultaneous removal of three tetracycline group antibiotics in co-existence in aquatic environments, including tetracycline (TC), oxytetracycline (OTC), chlortetracycline (CTC), and nitrous compounds in hydrogen (H2) and oxygen (O2) based membrane biofilm reactors (MBfRs). The treatment performances of MBfRs were comprehensively investigated by considering the effect of the hydraulic retention time (HRT) and surface loadings of tetracycline mixture. The results demonstrated that the average nitrification and denitrification efficiencies were 96% and 98% in H2-MBfR and O2-MBfR, respectively. The highest removal efficiencies for TC, OTC, and CTC in O2-MBfR were 52.5%, 54.83%, and 70.67%, while they were 92.5%, 90.5%, and 99.25% in H2-MBfR, respectively. The microbial analysis results showed that the dominant bacterial species in the biofilm of O2 and H2-based MBfRs belonged to the phyla Bacteroidetes and Proteobacteria. The findings of this study suggest that the MBfR process is an efficient alternative to remove tetracycline mixture and simultaneous nitrogen removal.
Keywords: Membrane biofilm reactor; Tetracycline antibiotics; Antibiotic removal; Nitrification-denitrification; Microbial community